A CRITICAL ANALYSIS OF THE OFFENCES OF A THIRD PARTY IN MARRIAGE (SALAM Digest: Syariah and Law Undergraduate Symposium, 2025)
The stability and harmony of the marital institution are increasingly threatened by the interference of third parties. Despite its prevalence, there is no standardized legal definition of a "third party" within the Malaysian legal framework. This study aims to identify the specific legal provisions addressing third-party interference in marriage, examine the enforcement procedures involved, and analyze the challenges faced in implementing these provisions. Adopting a qualitative research design, this study utilizes a case study approach and comprehensive data collection from scholarly articles, legal texts, and statutory provisions in Selangor. The findings reveal that the Syariah Criminal Offences (State of Selangor) Enactment 1995 provides specific legal recourse under Sections 32, 33, and 34. Furthermore, the study delineates the procedural workflow for addressing these offenses, beginning with complaints lodged at the Selangor Islamic Religious Office (JAIS), followed by investigations by religious enforcement officers, and culminating in prosecution. However, the research highlights significant hurdles in enforcement, primarily due to insufficient evidence, inconsistent witness testimonies, and complexities within the investigative process. Despite the rising incidence of marital scandals, the lack of public awareness and the absence of recorded prosecutions suggest that these legal provisions remain underutilized. This study concludes that enhanced legal literacy and more robust enforcement mechanisms are essential to protecting the sanctity of the household.